Smoking in pregnancy: some notes on the statistical controversy. Issue 1 (March 1977) - Goldstein, H
Abstract : The statistical evidence for a relationship between pregnancy smoking, birthweight, and perinatal mortality is critically examined. Some apparent discrepancies between and within different studies are resolved.